Evidence for an epistatic effect between TP53 R72P and MDM2 T309G SNPs in HIV infection: a cross-sectional study in women from South Brazil. - Fernando Pires Hartwig; Ludmila Gonçalves Entiauspe; Emily Montosa Nunes; Fernanda Martins Rodrigues; Tiago Collares; Fabiana Kömmling Seixas; Mariângela Freitas da Silveira (PLoS ONE)
Objective To investigate the associations of TP53 R72P and MDM2 T309G SNPs with HPV infection status, HPV oncogenic risk and HIV infection status. Design Cross-sectional study combining two groups (150 HIV-negative and 100 HIV-positive) of women. Methods Data was collected using a closed questionnaire. DNA was extracted from cervical samples. HPV infection status was determined by nested-PCR, and HPV oncogenic risk group by Sanger sequencing. Both SNPS were genotyped by PCR-RFLP. Crude and adjusted associations involving each exposure (R72P and T309G SNPs, as well as 13 models of epistasis) and each outcome (HPV status, HPV oncogenic risk group and HIV infection) were assessed using logistic regression. Results R72P SNP was protectively associated with HPV status (overdominant model), as well as T309G SNP with HPV oncogenic risk (strongest in the overdominant model). No epistatic model was associated with HPV status, but a dominant (R72P over T309G) protective epistatic effect was observed for HPV oncogenic risk. HIV status was strongly associated (risk factor) with different epistatic models, especially in models based on a visual inspection of the results. Moreover, HIV status was evidenced to be an effect mediator of the associations involving HPV oncogenic risk. Conclusions We found evidence for a role of R72P and T309G SNPs in HPV status and HPV oncogenic risk (respectively), and strong associations were found for an epistatic effect in HIV status. Prospective studies in larger samples are warranted to validate our findings, which point to a novel role of these SNPs in HIV infection.